Sentencing: principles and practice - Winocur, Erin (Emond Montgomery Publications Limited, 2024)
"The 2nd edition, as part of our "Criminal Law Series," continues to be a very practical, balanced, and concise treatment of all issues related to criminal sentencing. The book begins with general principles and then moves on to discuss pleas negotiations, procedure and advocacy in sentencing hearings, impact on the victim, types of sentences available, Charter considerations, the sentencing ruling itself, appellate issues, ancillary orders, and post sentencing issues. This edition includes a new chapter on specific offences."– Provided by publisher.